Marine conservation biology : (Island Press, 2005)
Marine Conservation Biology brings together for the first time in a single volume leading experts from around the world to apply the lessons and thinking of conservation biology to marine issues. Contributors including James M. Acheson, Louis W. Botsford, James T. Carlton, Kristina Gjerde, Selina S. Heppell, Ransom A. Myers, Julia K. Parrish, Stephen R. Palumbi, and Daniel Pauly offer penetrating insights on the nature of marine biodiversity, what threatens it, and what humans can and must do to recover the biological integrity of the world's estuaries, coastal seas, and oceans.